A novel serum extracellular vesicle protein signature to monitor glioblastoma tumor progression. Issue 2 (17th September 2022) - Tzaridis, Theophilos; Weller, Johannes; Bachurski, Daniel; Shakeri, Farhad; Schaub, Christina; Hau, Peter; Buness, Andreas; Schlegel, Uwe; Steinbach, Joachim‐Peter; Seidel, Clemens; Goldbrunner, Roland; Schäfer, Niklas; et al.
Abstract: Detection of tumor progression in patients with glioblastoma remains a major challenge. Extracellular vesicles (EVs) are potential biomarkers and can be detected in the blood of patients with glioblastoma. In our study, we evaluated the potential of serum‐derived EVs from glioblastoma patients to serve as biomarker for tumor progression. EVs from serum of glioblastoma patients and healthy volunteers were separated by size exclusion chromatography and ultracentrifugation. EV markers were defined by using a proximity‐extension assay and bead‐based flow cytometry. Tumor progression was defined according to modified RANO criteria. EVs from the serum of glioblastoma patients (n = 67) showed an upregulation of CD29, CD44, CD81, CD146, C1QA and histone H3 as compared to serum EVs from healthy volunteers ( P value range: <.0001 to .08). For two independent cohorts of glioblastoma patients, we noted upregulation of C1QA, CD44 and histone H3 upon tumor progression, but not in patients with stable disease. In a multivariable logistic regression analysis, a combination of CD29, CD44, CD81, C1QA and histone H3 correlated with RANO‐defined tumor progression with an AUC of 0.76. Measurement of CD29, CD44, CD81, C1QA and histone H3 in serum‐derived EVs of glioblastoma patients, along with standard MRI assessment, has the potential to improve detection of true tumor progression and thus could be a useful biomarker for clinical decision making. Abstract : What's new? It is challenging to detect tumor progression in glioblastoma. Here, the authors evaluated whether extracellular vesicles (EVs) circulating in the blood could serve as a reliable biomarker for tumor progression. They screened two independent cohorts including a total of 67 glioblastoma patients. Serum EVs collected from glioblastoma patients showed upregulation of CD29, CD44, CD81, CD146, C1QA and histone H3 relative to EVs from healthy volunteers. Among glioblastoma patients, tumor progression was accompanied by upregulation of C1QA, CD44 and histone H3, which was not observed in patients with stable disease.